Internalization of Religious Character Values Through the Habituation of Religious Activities at SMPIT Ar Risalah Sukoharjo - Khoirunissa, Khoirunissa; Jinan, Mutohharun (Journal of Educational Sciences, 2025)
Character education has a fundamental role in shaping a moral and noble generation. One important aspect of character education is the internalization of religious character values which is the foundation for the development of other positive characters. This study aims to describe and explore how the internalization of religious character values is carried out through the habituation of religious activities at SMPIT Ar-Risalah Sukoharjo. By using descriptive qualitative research method, this study analyzes students' involvement in various religious activities classified based on the frequency of implementation, namely daily, weekly, monthly, and yearly. The results show that the habituation of religious activities, such as morning dhikr, dhuha prayer, dhuhur prayer in congregation, and Islamic-based extracurricular activities, plays a role in shaping students' religious attitudes and behaviors.